Effects of application of transcranial electrical stimulation in the training process at elite athletes of various sports - Koryagina, Yu. V.; Roguleva, L. G.; Nopin, S. V.; Ter-Akopov, G. N. (Voprosy kurortologii, fizioterapii i lechebnoi fizicheskoi kultury, 2020)
Restoring and optimizing the psychofunctional state of the athlete`s body is an important area of sports medicine. Methods that allow you to quickly level psychoemotional and physical stress by influencing regulatory systems are interesting. Transcranial Direct Current Stimulation (tDCS) refers to such methods. Its use in sports requires testing and scientific justification. Purpose of the study. To study the tDCS influence, used in the training process, on the psychofunctional state of highly qualified athletes of various sports. Material and methods. 86 athletes aged 16 to 30 years old were examined. Their qualifications ranged from candidate master of sports to international master of sports of cyclic (track and field — 7 athletes, triathlon — 12), acyclic (weightlifting — 18) and opponent (karate — 22, rugby — 27) sports. The EEG study of electroencephalogram, heart rate variability and psychophysiological testing, ergospirometric stress testing on a treadmill were carried out to substantiate the tDCS effects. Results. The positive effect of the tDCS use is shown, which is substantiated by a significant change in physiological and psychophysiological parameters. An increase in the heart work economization, adaptive and mobilization body reserves, psychophysiological indicators was noted in triathletes after a course of 7 tDCS procedures. One tDCS in track and field athletes (according to stress testing data) helped to optimize the performance and increase the functional capabilities of the myocardium, reduce energy consumption during work. During the period of urgent recovery, tDCS contributed to the heart rate restoring acceleration, increase of the bringing in oxygen and flushing out carbon dioxide rate, and hemodynamics. The use of one procedure among acyclic sports athletes was effective for optimizing the psycho-functional state, reducing the tension of regulatory processes. After maximum muscle-strengthening exercises, the recovery processes accelerated and the CNS performance increased. In athletes of opponent sports (rugby, karate), the tDCS use helped to reduce the time of sensorimotor reactions and increase mental stability, optimize the brain functional state, and economize the heart work. Conclusion. The positive effect of tDCS is expressed in improving the psycho-functional state and working capacity, accelerating the recovery processes of athletes after physical exertion. In this connection, this method can be widely recommended for use as a regenerating and stimulating effect in medical and biological support in elite sports.